A Geopolitical Stake: Republic of Moldova Between the European Union and the Eurasian Union - Mircea-Cristian Ghenghea (CES Working Papers, 2014)
Following the initialling of the Vilnius Agreement from 28-29 November 2013, the Republic of Moldova seemed to have entered the path towards the European integration. The great failure for the Brussels' leaders was, by far, the Ukraine's refuse to sign the Association Agreement, a decision placed on the account of Moscow's influence and which proved once more the fact that the relations between the European Union and the Russian Federation have grown increasingly confrontational over the Eastern Partnership's countries. In the context of the unrests in Kiev at the beginning of 2014 and subsequently of the pro-Russian movements in the South and East of the Ukrainian state, the Republic of Moldova has acquired a special significance within the geopolitical situation of the region, being regarded as an outpost of what certain analysts already consider to be the "New Cold War".
Keywords: F50; F53; F54; 330; Republic of Moldova; geopolitics; European Union; Eurasian Union